Molecular Cloning and Functional Characterization of a Novel (Iso)flavone 4′,7-O-diglucoside Glucosyltransferase from Pueraria lobata - Wang, Xin; Fan, Rongyan; Li, Jia; Li, Changfu; Zhang, Yansheng (Frontiers in Plant Science, 2016)
Pueraria lobata roots accumulate a rich source of isoflavonoid glycosides, including 7-O- and 4'-O-mono-glucosides, and 4',7-O-diglucosides, which have numerous human health benefits. Although isoflavonoid 7-O-glucosyltranferases (7-O-UGTs) have been well characterized at molecular levels in legume plants, genes or enzymes that are required for isoflavonoid 4'-O- and 4',7-O-glucosylation have not been identified in P. lobata to date. Especially for the 4',7-O-di-glucosylations, the genetic control for this tailing process has never been elucidated from any plant species. Through transcriptome mining, we describe here the identification and characterization of a novel UGT (designated PlUGT2) governing the isoflavonoid 4',7-O-di-glucosylations in P. lobata. Biochemical roles of PlUGT2 were assessed by in vitro assays with PlUGT2 protein produced in Escherichia coli and analyzed for its qualitative substrate specificity. PlUGT2 was active with various (iso)flavonoid acceptors, catalyzing consecutive glucosylation activities at their O-4' and O-7 positions. PlUGT2 was most active with genistein, a general isoflavone in legume plants. Real-time PCR analysis showed that PlUGT2 is preferentially transcribed in roots relative to other organs of P. lobata, which is coincident with the accumulation pattern of 4'-O-glucosides and 4',7-O-diglucosides in P. lobata. The identification of PlUGT2 would help to decipher the P. lobata isoflavonoid glucosylations in vivo and may provide a useful enzyme catalyst for an efficient biotransformation of isoflavones or other natural products for food or pharmacological purposes.